FRI0123 Biologic monotherapy (BMT) as a treatment pattern in ra patients in a developing country. (23rd January 2014) - Mysler, E.; Alvarellos, A.; Borgia, A.; Eimon, A.; García Salinas, R.; Najún Dubos, L.; Re, L.; Siri, D.; Solé, J. P.; Sommerfleck, F.; Velasco Zamora, J.; Wiederhold, C.
Abstract : Background: In RA patients, where biological therapy is needed, combination therapy (CT) with a biological agent plus MTX remains the standard of care. However, in some scenarios (i.e. DMARD intolerance, non-compliance) BMT appears as a therapeutic option. Objectives: To assess the proportion of RA patients that is currently being treated with BMT in our country and to analyze the reasons behind this treatment pattern. Methods: This is a cross-sectional analysis of data obtained from medical charts revision of RA patients. Proportion of patients, reasons for BMT utilization, physician's satisfaction with BMT outcomes and main causes of DMARD discontinuation were assessed. Results: This investigation involved 1148 patients from 32 sites distributed around the country. Main demographic characteristics were: age 54 ± 13 years, 81% female, mean disease duration 12 ± 9 years. Patients receiving BMT represented 21.4% (CI 95%:19-23) of the sample size (246/1148 patients) Conclusions: A significant proportion of RA patients in our country are treated with BMT. BMT treatment seems to be an accepted therapeutic option in our medical community, both as initial therapy or as part of a sparing strategy. Patterns of BMT for RA patients in a developing country seem to be similar than those observed in developed countries. References: Soliman MM, et al. Ann Rheum Dis2011; 70: 583–589. Lee SJ, et al. J Rheumatol2009; 36:1161–7 Acknowledgements: Disclosure of Interest: E. Mysler Grant/research support from: Roche Argentina, A. Alvarellos Grant/research support from: Roche Argentina, A. Borgia Grant/research support from: Roche Argentina, A. Eimon Grant/research support from: Roche Argentina, R. García Salinas Grant/research support from: Roche Argentina, L. Najún Dubos Employee of: Roche Argentina, L. Re Employee of: Roche Argentina, D. Siri Grant/research support from: Roche Argentina, J. Solé Employee of: Roche Argentina, F. Sommerfleck Grant/research support from: Roche Argentina, J. Velasco Zamora Grant/research support from: Roche Argentina, C. Wiederhold Grant/research support from: Roche Argentina